Bioactivity test of compound (Hexa-Tetra Contana) from sponge (Callyspongia pseudoreticulata) AS antibacterial of withered Disease on potato plant (Ralstonia solanacearum) - M. NURDIN,; USMAN, (International Journal of Pharma and Bio Sciences, 2017)
Sponge is one of the marine organisms of coral reefs that is able to produce secondary metabolite compounds with varieties of bioactivity and structural variations; one of its biological activities is as an antimicrobial. This study is aiming to test the bioactivity of hexa-tetracontane compounds that have been isolated from sponge of Callyspongia pseudoreticulata. An antibacterial activity test was performed on the Ralstonia solanacearum bacteria found in potato by using agar diffusion method with the use of filter paper discs. The result of bioactivity of hexa-tetracontane compounds with varied concentrations; 400mg/mL, 500 mg/mL, 600mg/mL with incubation periode of 1 – 7 days, showing that the diameter of the inhibition zone is at the peak of the bacterial growth under the concentration of 400 mg/ml and incubation period of 7 days and the diameter of inhibition zone is 21,33 mm with great difference compared to the other concentrations.